The end of the American century? A short history of US foreign policy from World War II to the present - Schultz, David (Journal of the Belarusian State University. International Relations, 2022)
In 1941 H. Luce famously declared the arrival of the American century where the US would emerge as the dominant superpower in the world. After the end of World War II and then again in 1991 after the collapse of the Soviet Union, it looked in many ways like H. Luce’s prediction was correct. However the world today looks very different compared to 1945 or 1991. This article looks at the way the world and US foreign policy have evolved, contending that the foreign policy options for the United States are very different now and in the future from what they once were. Both the D. Trump and now J. Biden foreign policies are the result of these changes, and the article looks at some of the challenges facing the US going forward.